Optimalisasi Implementasi SIPD Melalui Klinik Akuntansi dan Dampaknya Terhadap Kualitas Laporan Keuangan Daerah: Pendekatan Kualitatif Di Kabupaten Tojo Una-Una - Naida, Nasrun (Multidisciplinary Journal of Education , Economic and Culture, 2025)
This study aims to identify the main obstacles in the implementation of the Regional Government Information System (SIPD) in the Accounting and Reporting (Aklap) module and analyze its impact on the quality of the Regional Government Financial Report (LKPD). A qualitative approach with a case study design was used, located in Tojo Una-Una Regency. Data were collected through in-depth interviews, participant observation, and documentation studies, and analyzed using the Miles and Huberman interactive model. The results show that the implementation of SIPD still faces obstacles, particularly limited technical competence of human resources, system disruptions, and a lack of ICT infrastructure. The Accounting Clinic plays a strategic role in bridging technical and conceptual gaps through consultation and training, which contributes to improving the quality of the LKPD, as reflected in the BPK's WTP opinion for 13 consecutive years. This study confirms that the Accounting Clinic is an effective institutional innovation in strengthening technical capacity and regional financial accountability. Sustainable institutionalization of the Accounting Clinic is needed through budget strengthening, human resource capacity building, and the development of contextual needs-based training.